Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmicb.2020.577501
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Experiences of Working With a Socio-Scientific Issues-Based Curriculum Unit Using Role-Playing to Negotiate Antibiotic Resistance

Abstract: The emergence and widespread of antibiotic-resistant pathogenic microorganisms are of great individual and societal relevance. Due to the complex and multilayered nature of the topic, antibiotic resistance (ABR) is the object of concern for several scientific fields, such as microbiology or medicine, and encompasses a broad range of political, economic, and social aspects. Thus, the issue related to antibiotic-resistant bacterial diseases offers an excellent platform for designing and implementing the teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…These relations can probably be explained by the impact of engaging with SSI in‐class. After an SSI‐based teaching intervention, students indicated that they find learning about SSI relevant for their future (Ke et al, 2020; Sagmeister et al, 2021). SSI‐based teaching has also been shown to positively impact students' collective efficacy (Guérin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These relations can probably be explained by the impact of engaging with SSI in‐class. After an SSI‐based teaching intervention, students indicated that they find learning about SSI relevant for their future (Ke et al, 2020; Sagmeister et al, 2021). SSI‐based teaching has also been shown to positively impact students' collective efficacy (Guérin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This facilitates by the second session of the worksheet. The "Activity 2: The Impact of Air Pollutant (cigarette smoke) towards The Respiratory System" resumes the socio-scientific debate where students were asked to mimic societal or political decision-making (Feierabend & Eilks, 2010), this study role-playing in the form of panel discussion which adopted and modified from Agell et al, (2015) and Sagmeister & Kapelari (2021).…”
Section: Inspiration and Expiration Buttonsmentioning
confidence: 99%
“…Genom SNI kan elever även utveckla kunskaper i naturvetenskap (Rietz, Jönsson & Lundström, 2021;Sagmeister et al, 2021;Venville & Dawson, 2010). I studien av Ekborg et al (2013) Enligt den tidigare forskning som beskrivits ovan ger SNI bland annat möjlighet att utveckla kritiskt tänkande, att se flera perspektiv och inse komplexitet, söka och hantera information, ansvarskännande, empati och vilja att agera.…”
Section: Rietz Et Alunclassified